Low-smoke flame-retardant ethylene propylene diene monomer composite material and preparation method thereof
By using a synergistic flame retardant system of cyclic olefin copolymers, modified aluminum hydroxide-magnesium hydroxide, phosphorus-nitrogen intumescent type and melamine-modified graphene-layered bimetallic hydroxide, the problems of flammability of EPDM rubber materials and performance degradation caused by traditional flame retardants have been solved, achieving the effects of low smoke, low toxicity, high flame retardancy and good processing performance.
Patent Information
- Application Number
- CN202511363728.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-23
- Publication Date
- 2025-12-05
AI Technical Summary
Existing EPDM rubber materials are flammable, producing large amounts of smoke and toxic gases when burned, and traditional flame retardants can impair mechanical and processing properties, making it difficult to meet high safety requirements.
A ternary synergistic flame retardant system is adopted, which consists of cyclic olefin copolymer, modified aluminum hydroxide-magnesium hydroxide flame retardant, phosphorus-nitrogen intumescent flame retardant and melamine-modified graphene-layered bimetallic hydroxide composite flame retardant. Through the synergistic effect of different flame retardant mechanisms, a strong thermal barrier and char layer are formed, reducing smoke density and maintaining the mechanical properties of the material.
It achieves a high-efficiency flame retardant effect with low smoke and low toxicity, while improving the processing fluidity and mechanical properties of the material to meet the requirements of high safety applications.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of high polymer composite materials, and more particularly relates to a low-smoke flame-retardant ethylene propylene diene monomer (EPDM) composite material and a preparation method thereof. BACKGROUND
[0002] EPDM has excellent aging resistance, ozone resistance, heat resistance, chemical resistance and electrical insulation performance, and is widely used in automobile parts, building waterproof materials, electric wires and cables and other fields. However, EPDM itself is flammable, and the limiting oxygen index (LOI) is usually only 18%-20%, a large amount of smoke and toxic gases are generated during combustion, and there is a phenomenon of melt dripping, which greatly limits its application in occasions with high safety requirements for material fire safety.
[0003] In order to improve the flame-retardant performance of EPDM, the traditional method is to use halogen-based flame retardants. However, it will release a large amount of toxic, corrosive gas and smoke during combustion, which poses a serious threat to the environment and human life safety. With the increasing awareness of environmental protection and safety, the flame-retardant performance and smoke density of materials are continuously improved in modern society, and the development of low-smoke and "halogen-free" flame-retardant technology has become an industry consensus and urgent demand.
[0004] At present, the main methods to improve the flame-retardant performance of halogen-free EPDM include adding inorganic flame retardants, phosphorus-nitrogen flame retardants and intumescent flame retardants. Among them, inorganic flame retardants such as aluminum hydroxide (ATH) and magnesium hydroxide (MDH) have become the most commonly used flame-retardant additives due to their halogen-free, low-smoke and non-toxic characteristics. However, a single inorganic flame retardant requires a high filling amount to achieve good flame-retardant effect, which will seriously damage the mechanical properties and processing performance of EPDM. The phosphorus-nitrogen flame-retardant system has poor compatibility with EPDM, poor processing fluidity, affects the stability of performance, and is difficult to meet the industrial production requirements. The intumescent flame retardant (IFR) has poor compatibility with EPDM, and the carbon layer formed has limited strength at high temperature and is easily damaged by flame, which limits the further improvement of its flame-retardant efficiency.
[0005] Therefore, it is of important practical significance and application value to develop a kind of ethylene propylene diene monomer composite material with excellent flame-retardant performance, low-smoke characteristics, good mechanical properties and processing performance, and a preparation method thereof. SUMMARY
[0006] The purpose of the present application is to provide a low-smoke flame-retardant ethylene propylene diene monomer composite material and a preparation method thereof, which have the characteristics of high-efficiency flame retardation and low smoke and low toxicity.
[0007] The purpose of the present application can be achieved by the following technical solutions: A low-smoke flame-retardant ethylene propylene diene monomer composite material, comprising the following components by weight: Ethylene propylene diene monomer rubber 100 parts; Cyclic olefin copolymer 5-8 parts; Modified aluminum hydroxide-magnesium hydroxide flame retardant 20-25 parts; Phosphorus-nitrogen intumescent flame retardant 15-20 parts; Melamine modified graphene-layer double metal hydroxide composite flame retardant 2-5 parts; Vulcanization system 3-10 parts, the vulcanization system includes zinc oxide 3-5 parts, stearic acid 1-2 parts, accelerator 1-2 parts and sulfur 0.5-1.5 parts; Processing aid 1-5 parts; The preparation method of the melamine modified graphene-layer double metal hydroxide composite flame retardant comprises the following steps: A1, using ion exchange method to prepare melamine intercalated layered double metal hydroxide composite; A2, grafting graphene on the surface of the melamine intercalated layered double metal hydroxide composite.
[0008] In the technical solution, the ethylene propylene diene monomer rubber (EPDM) is a synthetic rubber copolymerized by ethylene, propylene and a small amount of non-conjugated diene, the main chain of which is a saturated carbon-hydrogen structure, does not contain double bonds and does not contain polar substituents, and the molecular chain is extremely flexible.
[0009] The cyclic olefin copolymer (COC) as a processing modifier and a synergistic smoke suppressant has excellent optical properties, low moisture absorption, high chemical resistance and biocompatibility, and has good compatibility with EPDM when added to EPDM, and its low melt viscosity can effectively improve the processing fluidity of the entire blended system. More importantly, COC itself emits very low smoke when burning, and its introduction helps to reduce the overall smoke density of the composite material.
[0010] The mechanism of the inorganic flame retardant is to decompose at high temperature, release crystallization water, and absorb a large amount of heat, thereby reducing the surface temperature of the material; at the same time, the generated metal oxide can form an insulating layer on the surface of the material.
[0011] The intumescent flame retardant (IFR) is a high-efficiency halogen-free flame retardant system, which is usually composed of an acid source, a carbon source and a gas source. When heated, it can form a dense and porous expanded carbon layer on the surface of the material, effectively insulating heat, oxygen and combustible gas transmission, and playing an excellent flame-retardant role.
[0012] Melamine intercalated in the layered structure of layered double hydroxide can protect melamine flame retardant to a certain extent, avoiding the influence of high temperature on the flame retardant effect of melamine. Graphene is grafted on the surface of layered double hydroxide, and graphene has certain thermal conductivity. The heat conducted by graphene is conducted to the interior of layered double hydroxide, and then the heat is quickly dispersed.
[0013] Further, the ethylene propylene diene rubber raw rubber has a Mooney viscosity of 40-60 based on ML1+4, 125°C; and the ethylene content of the ethylene propylene diene rubber raw rubber is 60-70%.
[0014] The ethylene propylene diene rubber raw rubber is high ethylene content EPDM. The high ethylene content gives the EPDM molecular chain higher regularity and crystallinity, improves the thermal stability and mechanical strength of the material, and at the same time, the saturated main chain structure helps to reduce the generation of flammable cracking fragments during combustion.
[0015] Further, the modified aluminum hydroxide-magnesium hydroxide flame retardant is modified by a silane coupling agent.
[0016] Preferably, the mass ratio of aluminum hydroxide to magnesium hydroxide in the aluminum hydroxide-magnesium hydroxide flame retardant is 2-4:1; preferably 3:1.
[0017] Preferably, the silane coupling agent is KH-550.
[0018] Further, the specific preparation method of the modified aluminum hydroxide-magnesium hydroxide flame retardant is: After mixing aluminum hydroxide and magnesium hydroxide, 1-2% of the silane coupling agent based on the total mass of the two is added, and then stirred at 70-90°C for 1-3 hours, and then dried to obtain the modified aluminum hydroxide-magnesium hydroxide flame retardant.
[0019] Aluminum hydroxide (ATH) and magnesium hydroxide (MDH) have different thermal decomposition temperatures (ATH about 230-300°C, MDH about 360-490°C), and their combination can achieve "stepwise" decomposition, continuously releasing water vapor in a wider temperature range, thereby playing a role in heat absorption, cooling, and diluting combustible gas. After modification by a silane coupling agent, the polar hydroxyl groups on the surface of the inorganic filler are covered by non-polar long chains, significantly improving its dispersibility and interfacial bonding force in the EPDM matrix.
[0020] Further, the phosphorus-nitrogen intumescent flame retardant is a polyammonium polyphosphate-triazine charring agent flame retardant composed of polyammonium polyphosphate as an acid source and triazine charring agent as a carbon source and gas source.
[0021] Further, the mass ratio of polyammonium polyphosphate to triazine charring agent in the polyammonium polyphosphate-triazine charring agent flame retardant is 3-5:1; preferably 4:1.
[0022] Further, the triazine-based char former is a compound of melamine cyanurate and pentaerythritol.
[0023] Wherein, ammonium polyphosphate (APP) is used as acid source, which decomposes to produce polyphosphoric acid at high temperature, catalyzing the dehydration and carbonization of EPDM matrix; triazine-based char former (CFA) is used as efficient carbon source and gas source, which cooperates with APP to form a dense, stable and highly expanded porous carbon layer on the surface of the material, which has strong physical barrier effect and can effectively prevent the transfer of heat and oxygen, inhibiting the combustion process.
[0024] Further, the degree of polymerization n of the ammonium polyphosphate is greater than 1000.
[0025] Further, the mass ratio of graphene to layered double hydroxide in the melamine modified graphene-layered double hydroxide composite flame retardant is 1:1-3.
[0026] Further, in step A1, the preparation of melamine intercalated layered double hydroxide composite by ion exchange method comprises the following steps: A11, preparing anion intercalated magnesium aluminum layered double hydroxide by coprecipitation method: A12, preparing melamine intercalated magnesium aluminum layered double hydroxide by ion exchange method.
[0027] Further, the anion is phosphate ion, carbonate ion, nitrate ion or chloride ion.
[0028] Further, the anion intercalated magnesium aluminum layered double hydroxide is phosphate intercalated magnesium aluminum layered double hydroxide. The specific preparation method of steps A1 and A2 is: A11, preparing phosphate intercalated magnesium aluminum layered double hydroxide by coprecipitation method: Mg(NO3)2·6H2O and Al(NO3)3·9H2O are dissolved in deionized water to prepare a mixed salt solution A; NaH2PO4·2H2O is dissolved in deionized water to prepare a phosphate solution B; then solution A and solution B are mixed, and a pH adjuster is added dropwise to control the pH of the system to 10.0±0.2; after the dropwise addition is completed, the system is stirred for crystallization and then aged; after filtration and washing to neutral, phosphate intercalated magnesium aluminum layered double hydroxide (denoted as Mg-Al-PO4-LDH) is obtained; A12, preparing melamine intercalated magnesium aluminum layered double hydroxide by ion exchange method: The Mg-Al-PO4-LDH powder is ultrasonically dispersed in deionized water to obtain a colloidal solution of positively charged Mg-Al-PO4-LDH nanosheets; then a sodium melamine sulfonate solution is added, and after mixing, the mixture is placed in a 60-80°C water bath for reaction; after the reaction is completed, the mixture is filtered, washed, and dried to obtain melamine intercalated magnesium-aluminum layered double hydroxide (denoted as Mg-Al-MS-LDH); A2, grafting graphene on the surface of the melamine intercalated magnesium-aluminum layered double hydroxide: The Mg-Al-MS-LDH powder is ultrasonically dispersed in formamide, then a pre-activated graphene oxide dispersion is added, and the mixture is heated to 40-50°C and reacted under nitrogen protection to obtain the melamine modified graphene-layered double hydroxide composite flame retardant.
[0029] The two-dimensional sheet structure of graphene forms a physical "labyrinth effect" in the matrix, delaying the escape of flammable volatile substances and the invasion of oxygen. The layered double hydroxide (LDH) has phosphate ions intercalated by ion exchange method in advance, and when heated, the LDH not only releases water, but also in-situ catalyzes the metal oxides to form carbon, which cooperates with graphene to enhance the compactness and oxidation resistance of the carbon layer.
[0030] Further, the accelerator is CBS, TMTD or ZDBC. Among them, CBS is N-cyclohexyl-2-benzothiazole sulfenamide; TMTD is tetramethylthiuram disulfide; ZDBC is zinc dibutyl dithiocarbamate.
[0031] Further, the processing aid includes paraffin or low molecular weight polyethylene to further improve the flowability during mixing and extrusion.
[0032] Further, the processing aid further includes 0.5-1 parts of antioxidant, 1-2 parts of lubricant, and 0.5-1 parts of anti-aging agent.
[0033] The preparation method of the low-smoke flame-retardant EPDM composite material includes the following steps: S1, adding EPDM raw rubber and cyclic olefin copolymer into a plasticizing machine for plasticizing; S2, adding modified aluminum hydroxide-magnesium hydroxide flame retardant, phosphorus-nitrogen intumescent flame retardant, nano-composite flame retardant, processing aid, and zinc oxide and stearic acid in the vulcanization system in batches, continuing to mix, then discharging at 130-140°C to obtain a mixed rubber; S3, performing thin pass, rolling, cooling on the mixed rubber on an open mill, adding accelerator and sulfur in the vulcanization system, mixing at a temperature below 90°C, and then cutting the rubber sheet to obtain a rubber sheet; S4, vulcanizing and molding the film at 160-170 DEG C, 10-20 MPa, and then cooling and demolding to obtain the ethylene-propylene-diene rubber composite material.
[0034] Use of the ethylene-propylene-diene rubber composite material as described above in the preparation of wire and cable sheaths, vehicle interior parts, building sealing strips, or electronic and electrical housings.
[0035] Advantages of the present application: (1) The present application reduces the smoke emission tendency from the base layer by compounding ethylene-propylene-diene rubber raw rubber with a small amount of cyclic olefin copolymer, and cooperates with the ternary synergistic flame-retardant system composed of "inorganic flame retardant-phosphorus-nitrogen intumescent flame retardant-nano composite flame retardant", the ternary synergistic flame-retardant system can effectively delay the decomposition of the material through the synergistic effect of different flame-retardant mechanisms, and form a strong heat barrier, achieving high-efficiency flame-retardant effect at a lower addition amount, while improving the processing fluidity of the material and ensuring good interface bonding between the filler and the base, so that the composite material can maintain good mechanical properties while achieving high flame retardance, meeting the application requirements.
[0036] (2) The base material of the ethylene-propylene-diene rubber composite material of the present application selects high ethylene content ethylene-propylene-diene rubber raw rubber, which has a high proportion of saturated structures in the molecular chain, can improve the thermal stability of the material and reduce the release of flammable gas during combustion; at the same time, a small amount of cyclic olefin copolymer is used to improve the processing fluidity of the ethylene-propylene-diene rubber and assist in reducing the smoke density of the overall material.
[0037] (3) The flame-retardant system of the present application adopts a ternary synergistic system of "inorganic flame retardant-phosphorus-nitrogen intumescent flame retardant-nano composite flame retardant", which takes into account the flame-retardant efficiency and low smoke properties, wherein the inorganic flame retardant selects a compound of aluminum hydroxide and magnesium hydroxide modified by a silane coupling agent, which decomposes step by step at high temperature, continuously releases crystallization water to absorb heat and reduce temperature, and the generated Al2O3 and MgO composite layer can block the transmission of oxygen and heat, reducing smoke generation. The phosphorus-nitrogen intumescent flame retardant uses a compound of ammonium polyphosphate and a triazine charring agent, ammonium polyphosphate as an acid source releases phosphoric acid at high temperature to catalyze the carbonization of ethylene-propylene-diene rubber; the triazine charring agent as a carbon source and gas source cooperates with ammonium polyphosphate to form a porous intumescent carbon layer, further blocking the flame propagation, and the system does not release halide during combustion, with extremely low smoke toxicity. The nano composite flame retardant uses a melamine modified graphene-layered double hydroxide composite nano flame retardant, the two-dimensional sheet structure of graphene can physically block the diffusion of flammable gas, and the layered double hydroxide enhances the catalytic carbonization effect through interlayer anion exchange, thereby improving the limiting oxygen index of ethylene-propylene-diene rubber. DETAILED DESCRIPTION
[0038] In order to further illustrate the technical means and effects adopted by the present application to achieve the predetermined object, the specific embodiments, structures, features and effects according to the present application are described in detail below in combination with examples.
[0039] The raw materials used are described as follows: ① Ethylene-propylene-diene rubber: purchased from Dow Chemical, ethylene content 65%, Mooney viscosity (ML1+4, 125℃) 55.
[0040] ② Cyclic olefin copolymer: purchased from Japan Zeon, glass transition temperature 105℃.
[0041] ③ Modified aluminum hydroxide-magnesium hydroxide flame retardant: modified by KH-550, mass ratio of aluminum hydroxide to magnesium hydroxide 3:1; average particle size of aluminum hydroxide 1.5 μm; average particle size of magnesium hydroxide 1.0 μm. The specific preparation method is as follows: Mix aluminum hydroxide and magnesium hydroxide, put them in a high-speed mixer, spray 1.5% of the total mass of the ethanol solution of silane coupling agent KH-550, stir and react at 80℃ for 2 hours, then dry at 110℃ for 4 hours, grind to an average particle size of 10-20 nm, and obtain the modified aluminum hydroxide-magnesium hydroxide flame retardant.
[0042] ④ Phosphorus-nitrogen intumescent flame retardant: ammonium polyphosphate is used as an acid source, the polymerization degree of ammonium polyphosphate n≈1500, the decomposition temperature >280℃; triazine charring agent is used as a carbon source and gas source, the triazine charring agent is a compound of melamine cyanurate and pentaerythritol with a mass ratio of 1:1. The preparation method is as follows: Mix ammonium polyphosphate and triazine charring agent with a mass ratio of 4:1 in a high-speed mixer with a rotation speed of 1000 rpm for 15 minutes, and then pass through a 100-mesh sieve to obtain the phosphorus-nitrogen intumescent flame retardant.
[0043] ⑤ Melamine modified graphene-layer double metal hydroxide composite flame retardant: the layer double metal hydroxide is phosphate intercalated magnesium aluminum layer double metal hydroxide (Mg-Al-PO4-LDH), and the mass ratio of graphene to Mg-Al-PO4-LDH is 1:2. The specific preparation method is as follows: A11, prepare phosphate intercalated LDH by coprecipitation method: A11-1, dissolve Mg(NO3)2·6H2O and Al(NO3)3·9H2O with a molar ratio of 2:1 in deionized water to prepare a mixed salt solution A with a concentration of 0.9 mol / L; dissolve NaH2PO4·2H2O in deionized water to prepare a phosphate solution B with a concentration of 0.5 mol / L; A11-2, under the condition of nitrogen protection and 60℃ constant temperature, solution A and solution B were simultaneously and slowly added into the reaction kettle, and 2 mol / L NaOH solution was added at the same time, and the pH of the system was controlled at 10.0±0.2; A11-3, after the completion of the dropwise addition, the crystallization was continued for 2 hours, and then the aging was continued for 6 hours; A11-4, the filtration was performed, and the Mg-Al-PO4-LDH was obtained by washing with deionized water until the pH of the filtrate was 7, and then vacuum drying at 80℃ for 12 hours.
[0044] A12, the melamine intercalated Mg-Al layered double hydroxide was prepared by ion exchange method, and the graphene-Mg-Al-PO4-LDH nanocomposite flame retardant was prepared by electrostatic self-assembly: A12-1, the Mg-Al-PO4-LDH powder was dispersed in deionized water, and ultrasonic stripping was performed at room temperature for 2 hours to obtain a Mg-Al-PO4-LDH nanosheet colloidal solution with a positive charge and a concentration of 1 g / L; A12-2, under magnetic stirring, 3 g / L of melamine sodium sulfonate solution was added, and after mixing, the mixture was placed in a 70℃ water bath for reaction. After the reaction was completed, the filtration was performed, and the Mg-Al-MS-LDH was obtained by washing with deionized water for 3 times, and then vacuum drying at 80℃ for 12 hours, and then grinding through a 400 mesh sieve.
[0045] A2, the graphene was grafted on the surface of the melamine intercalated Mg-Al layered double hydroxide: The Mg-Al-MS-LDH powder was dispersed in 1 g / L formamide, and ultrasonic stripping was performed at room temperature for 4 hours to obtain a Mg-Al-MS-LDH nanosheet colloidal solution, and then 0.5 g / L of pre-activated graphene oxide water dispersion was added, and the temperature was increased to 40-50℃, and the reaction was performed under nitrogen protection to obtain the melamine modified graphene-layered double hydroxide composite flame retardant.
[0046] The preparation steps of the pre-activated graphene oxide water dispersion are as follows: the graphene oxide was dispersed in deionized water, and sodium hypochlorite (NaClO) with effective chlorine ≥10% was added, and the reaction was performed at 60℃ for 2 hours, and then dialysis was performed until the pH was 6.5, and the carboxylated graphene oxide water dispersion with a concentration of 0.5 g / L was prepared; then, 0.1 parts of carbodiimide (EDC) and 0.06 parts of N-hydroxysuccinimide (NHS) were added into the carboxylated graphene oxide water dispersion in an ice water bath at 0℃, and the activation was performed for 30 min to obtain the pre-activated graphene oxide water dispersion.
[0047] The ternary ethylene propylene rubber composite material was prepared according to the formula shown in Table 1, and the unit was weight part. Among them, examples 1-3 were different formula examples of the application.
[0048] Table 1 The preparation method of the composite material is as follows: S1, add the raw EPDM rubber and the cyclic olefin copolymer into the internal mixer, set the temperature to 100-110°C, and the rotation speed to 50-60 rpm, and plasticize for 2-5 minutes; S2, add the zinc oxide and stearic acid in the vulcanization system, the processing aid, the modified aluminum hydroxide-magnesium hydroxide flame retardant, the phosphorus-nitrogen intumescent flame retardant, and the melamine modified graphene-layer double metal hydroxide composite flame retardant in batches, continue to mix for 5-10 minutes, and then discharge at 130-140°C to obtain the mixed rubber; S3, perform thin pass and roll mixing of the mixed rubber on the open mill, and control the roller temperature below 80°C; after the rubber cools down and is wrapped, add the accelerator and sulfur in the vulcanization system, mix, and then lay the rubber sheet, and store for 22-26 hours to obtain the rubber sheet; S4, place the rubber sheet in the mold of the flat vulcanizing machine, vulcanize at 160-170°C and 10-20 MPa for 10-15 minutes, cool and demold, and obtain the EPDM rubber composite material.
[0049] Comparative Example 1 Compared with Example 1, the difference of the present comparative example is that the present comparative example does not add the cyclic olefin copolymer, and correspondingly, the weight part of the raw EPDM rubber is 106 parts, and the rest of the components, the preparation steps and parameters are consistent.
[0050] Comparative Example 2 Compared with Example 1, the difference of the present comparative example is that the present comparative example replaces the modified aluminum hydroxide-magnesium hydroxide flame retardant with 24 parts by weight of aluminum hydroxide and 8 parts by weight of magnesium hydroxide, i.e. without modification treatment. The rest of the components, the preparation steps and parameters are consistent.
[0051] Comparative Example 3 Compared with Example 1, the difference of the present comparative example is that the present comparative example replaces the modified aluminum hydroxide-magnesium hydroxide flame retardant with the modified aluminum hydroxide flame retardant, i.e. only contains one inorganic flame retardant. The rest of the components, the preparation steps and parameters are consistent.
[0052] Comparative Example 4 Compared with Example 1, the difference of the present comparative example is that the present comparative example does not add the phosphorus-nitrogen intumescent flame retardant, and correspondingly, the weight part of the modified aluminum hydroxide-magnesium hydroxide flame retardant is 38.2 parts, and the weight part of the graphene-Mg-Al-PO4-LDH nano composite flame retardant is 4.3 parts, and the rest of the components, the preparation steps and parameters are consistent.
[0053] Comparative Example 5 The difference between the comparative example and the example 1 is that the melamine modified graphene-layer double metal hydroxide composite flame retardant is replaced by the DOPO derivative modified graphene-layer double metal hydroxide composite flame retardant in the comparative example. The preparation of the DOPO derivative modified graphene-layer double metal hydroxide composite flame retardant is basically the same as the “melamine modified graphene-layer double metal hydroxide composite flame retardant” in the foregoing part, the only difference is that the “sodium melamine sulfonate solution” is changed to “dispersion of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-ethanol 10-oxide” in the preparation process of the “melamine modified graphene-layer double metal hydroxide composite flame retardant”. Here, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-ethanol 10-oxide has a CAS number of 63562-41-4, denoted as ODOPM.
[0054] The dispersion of ODOPM is prepared as follows: Dissolve ODOPM in anhydrous ethanol to form an ODOPM solution; then pour the ODOPM solution into the sodium lauryl sulfonate aqueous solution and ultrasonically disperse to obtain an ODOPM dispersion. The remaining components, preparation steps and parameters are consistent.
[0055] The samples prepared in examples 1-3 and comparative examples 1-5 were respectively subjected to the following performance tests.
[0056] (1) Mechanical property test According to the GB / T528-2009 standard, a universal material testing machine was used to test the tensile strength and elongation at break of the sample. The tensile strength = maximum tension force / initial cross-sectional area of the sample gauge section. The elongation at break = (length of the gauge section at break - initial length of the gauge section) / initial length of the gauge section x 100%.
[0057] (2) Limiting oxygen index (LOI) test According to the GB / T2406.2-2009 standard, an oxygen index tester was used for the test. The sample was vertically fixed in the combustion cylinder, and oxygen and nitrogen mixed gas stream was introduced from the bottom, the top end of the sample was ignited, the oxygen concentration was adjusted, and the combustion behavior of the sample was observed. When the sample can just maintain steady combustion, the volume percentage of oxygen in the mixed gas stream at this time is the limiting oxygen index of the material.
[0058] (3) Vertical burning test (UL-94) According to GB / T2408-2008 standard, the sample with thickness of 3.2mm is tested. The Bunsen burner is used to apply flame to the lower end of the sample for 10 seconds with the flame being 20±1mm high and being 20° to the vertical direction, then the flame is removed, and the flaming combustion time of the sample is recorded; the flame is applied again for 10 seconds, and the second flaming combustion time and non-flaming combustion time are recorded after the flame is removed. According to the combustion time, dripping condition and other indexes, the flame retardant grade of the material is divided into HB, V-2, V-1, V-0.
[0059] (4) Smoke density test According to GB / T8627-2007 standard, the smoke density box test is used to record the maximum smoke density (SDR).
[0060] (5) Processing performance test According to GB / T1232.1-2000, the Mooney viscometer is used to test the Mooney viscosity (ML1+4, 100℃) of the mixed rubber.
[0061] The test results are shown in Table 2.
[0062] Table 2 From the test results in Table 1, it can be seen that, compared with Comparative Examples 1-5, the LOI of Examples 1-3 is more than 31%, the UL-94 test reaches V-0 level, the maximum smoke density SDR is controlled to be below 100, at the same time, the tensile strength of the material is >11MPa, and the elongation at break is >350%, which shows good mechanical properties and moderate processing viscosity, indicating that the comprehensive performance of the composite material of the application is excellent. In Comparative Example 1, the cycloolefin copolymer is lacking, and the mechanical properties, processing viscosity and smoke density are all obviously deteriorated; in Comparative Examples 2-5, the change of the flame retardant causes the effect of the limiting oxygen index and the smoke density to be weakened, and most of them cannot maintain V-0 level, highlighting the superiority of the synergistic compounding between the ternary system of “inorganic flame retardant-phosphorus-nitrogen intumescent flame retardant-nano composite flame retardant”.
[0063] The above is only a preferred embodiment of the application, and does not limit the application in any form. Although the application has been disclosed as above with a preferred embodiment, it is not intended to limit the application. Any person skilled in the art can make some changes or modifications to the above disclosed technical content without departing from the scope of the technical solution of the application, and any equivalent embodiments with equivalent changes and modifications made to the above embodiments according to the technical essence of the application are still within the scope of the technical solution of the application.
Claims
1. A low-smoke flame-retardant EPDM rubber composite material, characterized in that, The following components are included by weight: 100 parts of EPDM raw rubber; 5-8 parts of cyclic olefin copolymer; 20-25 parts of modified aluminum hydroxide-magnesium hydroxide flame retardant; 15-20 parts of phosphorus-nitrogen intumescent flame retardant; 2-5 parts of melamine-modified graphene-layered bimetallic hydroxide composite flame retardant; The vulcanization system comprises 3-10 parts of zinc oxide, 1-2 parts of stearic acid, 1-2 parts of accelerator, and 0.5-1.5 parts of sulfur. Processing aids 1-5 parts; The preparation method of the melamine-modified graphene-layered bimetallic hydroxide composite flame retardant includes the following steps: A1. A melamine-intercalated layered bimetallic hydroxide composite was prepared by ion exchange method; A2. Graphene is grafted onto the surface of the melamine-intercalated layered bimetallic hydroxide composite.
2. The low-smoke flame-retardant EPDM rubber composite material according to claim 1, characterized in that, The EPDM raw rubber has a Mooney viscosity of 40-60 at 125°C based on ML1+4; the ethylene content of the EPDM raw rubber is 60-70% by mass.
3. The low-smoke flame-retardant EPDM rubber composite material according to claim 1, characterized in that, The modified aluminum hydroxide-magnesium hydroxide flame retardant is modified with a silane coupling agent; The mass ratio of aluminum hydroxide to magnesium hydroxide in the aluminum hydroxide-magnesium hydroxide flame retardant is 2-4:
1.
4. The low-smoke flame-retardant EPDM rubber composite material according to claim 3, characterized in that, The specific preparation method of the modified aluminum hydroxide-magnesium hydroxide flame retardant is as follows: After mixing aluminum hydroxide and magnesium hydroxide, add 1-2% of silane coupling agent by mass, stir and react at 70-90℃ for 1-3 hours, and then dry to obtain modified aluminum hydroxide-magnesium hydroxide flame retardant.
5. The low-smoke flame-retardant EPDM rubber composite material according to claim 1, characterized in that, The phosphorus-nitrogen intumescent flame retardant is a polyphosphate-triazine charring agent flame retardant composed of ammonium polyphosphate as an acid source and triazine charring agent as a carbon source and gas source. The mass ratio of ammonium polyphosphate to triazine charring agent in the ammonium polyphosphate-triazine charring agent flame retardant is 3-5:
1.
6. The low-smoke flame-retardant EPDM rubber composite material according to claim 1, characterized in that, The mass ratio of graphene to layered bimetallic hydroxide in the melamine-modified graphene-layered bimetallic hydroxide composite flame retardant is 1:1-3.
7. The low-smoke flame-retardant EPDM rubber composite material according to claim 1, characterized in that, In step A1, the preparation of the melamine-intercalated layered bimetallic hydroxide composite using the ion exchange method includes the following steps: A11. Preparation of anion-intercalated magnesium-aluminum layered bimetallic hydroxides by co-precipitation method: A12. A melamine-intercalated magnesium-aluminum layered bimetallic hydroxide was prepared by ion exchange.
8. The low-smoke flame-retardant EPDM rubber composite material according to claim 1, characterized in that, The accelerator is CBS, TMTD, or ZDBC; the processing aid includes paraffin or low molecular weight polyethylene.
9. A method for preparing a low-smoke flame-retardant EPDM rubber composite material as described in any one of claims 1-8, characterized in that, The preparation method includes the following steps: S1. Add EPDM raw rubber and cyclic olefin copolymer to a mixer and plasticize. S2. Add modified aluminum hydroxide-magnesium hydroxide flame retardant, phosphorus-nitrogen intumescent flame retardant, nano-composite flame retardant, processing aids, and zinc oxide and stearic acid in the vulcanization system in batches, continue mixing, and then discharge at 130-140℃ to obtain mixed rubber. S3. The mixed rubber is passed through a rolling mill, turned over, cooled, and the accelerator and sulfur in the vulcanization system are added. After mixing at a temperature below 90°C, the mixture is sheeted to obtain rubber sheets. S4. The film is vulcanized at 160-170℃ and 10-20MPa, and then cooled and demolded to obtain EPDM rubber composite material.
10. The application of the EPDM rubber composite material as described in any one of claims 1-8 in the preparation of wire and cable sheaths, vehicle interior parts, building sealing strips, or electronic and electrical enclosures.
Citation Information
Patent Citations
Low smoke halogen-free flame retardant ethylene-propylene-diene rubber and preparation method by extrusion molding thereof
CN101704976A
Flame-retardant automobile rubber sealing strip
CN105111599A
Low-smoke zero-halogen ethylene-propylene-diene monomer rubber composition and preparation method
CN110746706A
Flame-retardant polyolefin material as well as preparation method and application thereof
CN114752137A
Flame-retardant compound and preparation method thereof
CN115505201A
Cited By
Flame-retardant anti-aging ethylene-propylene copolymer composition and preparation method thereof
CN121628252A